The Placebo Phenomenon: Implications for the Ethics of Shared Decision-Making - Brody, Howard (Springer-Verlag, 2012)
Recent research into the placebo effect has implications for the ethics of shared decision-making (SDM). The older biomedical model views SDM as affecting which therapy is chosen, but not the nature or likelihood of any health outcomes produced by the therapy. Research indicates, however, that both the content and manner in which information is shared with the patient, and the patient’s experience of being involved in the decision, can directly alter therapeutic outcomes via placebo responses. An ethical tension is thereby created between SDM aimed strictly and solely at conveying accurate information, and “outcome engineering” in which SDM is adapted toward therapeutic goals. Several practical strategies mitigate this tension and promote respect for autonomous decision-making while still utilizing the therapeutic potential of SDM.